Corporate e-learning an inside view of IBM's solutions - Tai, Luther, 1948- (Oxford University Press, 2008)
The author describes in depth how e-learning programs are developed and instituted, and how their effectiveness is measured, from the perspective of practising e-learning professionals at IBM, an early and liberal user of e-learning technologies to train their global workforce.